Le paysagisme : source et ressource pour l’urbanisme ? - Benoît Romeyer (Projets de Paysage)
Although in France urban design and landscape architecture are two different disciplines, the boundaries between them tend to be blurred, and in some regards they are porous. Based on a review of the literature of the different forms and modes of “cross-fertilisation” between urban design and landscape architecture observed in the past, this article offers a classification of their major associated fields of expression. It successively identifies and defines the urban design practises predominantly influenced by the “plant” component, and which involve the notions of the embellishment, re-enchantment and "re-naturing" of open spaces, and the practises that specifically concern the landscape component of the parks, “green and blue” infrastructures, and “extra-urban” spaces of different neighbourhoods, suburbs and garden cities. Whether analysed separately or together, these elements constitute resources that may be reconsidered and re-used in order to establish more balanced relationships with the elements surrounding us in our contemporary urban construct.